‘Keine Rührung – Erkenntnis!’: The Aesthetics of Espressivo in the ‘Performance Theories’ of Arnold Schoenberg and Rudolf Kolisch - Mattes, Arnulf Christian (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2013)
Schoenberg’s concept of the work as the presentation (Darstellung) of the ‘musical idea’(Gedanke) entails that the work is considered a vehicle by means of which the composer shares musical ideas with the performer and the listener in one particular aesthetic event. This requires a performer who understands how to make the ‘musical idea’ comprehensible for the audience. One of the few to gain Schoenberg’s respect as a ‘good’ performer was the violinist Rudolf Kolisch. He belonged to the enthusiastic group of young Viennese musicians who joined Schoenberg’s ‘Society for Private Musical Performances’ following World War I. This article examines central categories in Schoenberg’s aesthetic thought in their historical context, categories such as ‘musical idea’, ‘expression’ and ‘progression’. The objective of this article is to shed light on how Schoenberg’s aesthetic concepts guide the principles of Kolisch’s ‘performance theory’, moving beyond the dichotomy between fidelity to the text and expressive freedom. The discussion of the Schoenberg school’s performance style leads to the question of whether Kolisch’s ‘Wiener espressivo’ is still relevant for today’s performers, in a time when technically perfect renditions of scores are considered a matter of course.